PRDX4 and Its Roles in Various Cancers. (19th July 2019) - Jia, Wenqiao; Chen, Pengxiang; Cheng, Yufeng
Reactive oxygen species play a vital role in cell survival by regulating physiological metabolism and signal transduction of cells. The imbalance of oxidant and antioxidant states induces oxidative stress within a cell. Redox regulation and oxidative stress are closely related to survival and proliferation of stem cells, cancer cells, and cancer stem cells. Peroxiredoxin 4, a typical endoplasmic reticulum-resident 2-Cys antioxidant of peroxiredoxins, can fine-tune hydrogen peroxide catabolism which affects cell survival by affecting redox balance, oxidative protein folding, and regulation of hydrogen peroxide signaling. Recent studies revealed the overexpression of peroxiredoxin 4 in several kinds of cancers, such as breast cancer, prostate cancer, ovarian cancer, colorectal cancer, and lung cancer. And it has been demonstrated that peroxiredoxin 4 causally contributes to tumorigenesis, therapeutic resistance, metastasis, and recurrence of tumors. In this article, the characteristics of peroxiredoxin 4 in physiological functions and the cancer-related research progress of mammalian peroxiredoxin 4 is reviewed. We believe that peroxiredoxin 4 has the potential of serving as a novel target for multiple cancers.